(untitled) (Boston, 2008)
This Thirty-First Edition of ANNUAL EDITIONS: ANTHROPOLOGY provides convenient, inexpensive access to current articles selected from the best of the public press. Organizational features include: an annotated listing of selected World Wide Web sites; an annotated table of contents; a topic guide; a general introduction; brief overviews for each section; a topical index; and an instructor’s resource guide with testing materials
Keywords: Anthropology,Nhân chủng học